Comparison of Surgical Outcomes in Large Fibroids With and Without Preoperative Ureteric Stenting - Kausar Masoom, Syed Azra, Nida Arif, Sannia Nasir, Rafia Asif, Arfa Khalil (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Ureter injury is a severe side effect of gynecologic surgery, especially in the circumstances when the pelvic anatomy is deformed with large uterine or cervical fibroids which makes operative procedures harder. Prophylactic ureteric stenting is also suggested to improve intraoperative recognition of the ureter but its widespread implementation is questionable. Purpose: To compare the results of intraoperative and postoperative outcomes in patients who undergo surgery to remove large fibroids with both preoperative ureteric stenting and validity. Methodology: This was a comparative study of observational design involving 300 women who had a uterine size of 12 weeks and above and underwent either myomectomy or hysterectomy. The patients were assigned into two groups Group A (stented, n = 150) and Group B (non-stented, n = 150). Ureteric and bladder injuries were the main outcomes. Secondary outcomes were the duration of operation, estimated blood loss, 30 day postoperative complications and hospitalization. The appropriate comparative tests were used to perform statistical analysis and p < 0.05 was considered significant. Findings: The incidence of ureteric injury was 1.3 per cent in the stented group and 6.7 per cent in the non-stented group. The injuries of the bladder were 0.7 and 5.3, respectively. The average time of operation and blood loss was significant in the stented group. The total postoperative complications were 8.0 and 16.0 percent in the stented and non-stented groups respectively. Conclusion: There is a relationship between a reduction in urinary tract injury and enhanced perioperative outcomes with selective preoperative ureteric stenting and large fibroid surgery. It should not be used routinely but rather it should be used risk-based. Keywords: Ureteric injury, Prophylactic ureteric stenting, Large uterine fibroids, Cervical fibroids, Hysterectomy, Myomectomy, Urinary tract injury, Perioperative outcomes